LEGISLATIVE ACTIVITY IN UKRAINE ABOUT POSSIBLE CHANGES TO THE CPC - Malyarchuk, Nazar V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The paper investigates the problem of legal regulation, proposed by the Law of Ukraine «On Amendments to the Criminal Procedure Code of Ukraine (on improvement of the mechanisms to ensure the tasks of criminal proceedings)». Based on the analysis, it was found that some change in the bill is irrationality. So according to this we had presented a number of proposals to perfecting of the certain provisions of the bill.